Analysis of the Impact of Case-Based Learning Methods in Enhancing Students' Legal Analysis Skills - Mustaqim, Dede Al (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The skill of legal analysis is one of the essential skills that law students must possess. This skill can be honed through various learning methods, one of which is the case-based learning method. This method provides students with the opportunity to analyze legal cases in a thorough and comprehensive manner. This research aims to analyze the impact of case-based learning method on enhancing the legal analysis skills of students. The study was conducted on students majoring in Sharia Economic Law at IAIN Syekh Nurjati Cirebon in their sixth semester, involving a total of 40 students. The research method employed was qualitative with a case study approach. The results indicate that the case-based learning method has a positive impact on improving the legal analysis skills of students. Students who participated in case-based learning demonstrated improvements in their ability to understand legal issues, apply legal theories, think critically and logically, and solve legal problems. Case-based learning can be implemented in various forms, such as case simulations, case studies, and moot court. Legal education practitioners can choose the most suitable form of learning based on the learning material and the characteristics of the students.